2014
DOI: 10.1590/s1982-56762014000400005
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Phytophthora infestans in Solanum tuberosum landraces in Southern Chile

Abstract: The objective of this work was to evaluate the resistance of 30 Chilean potato landraces to natural infection by Phytophthora infestans during two growing seasons in Southern Chile. Control cultivars were 'Désirée', which has moderate susceptibility to late blight, and 'Karú', which is characterized by moderate resistance to the disease. The response of the potato landraces to late blight infection was assessed weekly by scoring the percentage of foliage destruction during the growing season. Subsequently, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
7
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 22 publications
5
7
1
2
Order By: Relevance
“…For instance, Haynes and Christ (1999) reported much higher heritability estimates for late blight resistance (0.8), but this study was based on diploid hybrids. For the same trait, estimates of heritability obtained using tetraploid genotypes are closer to the ones reported here (ranging from 0.31 to 0.69, Pajerowska-Mukhtar et al 2009 ; Solano et al 2014 ).…”
Section: Discussionsupporting
confidence: 80%
“…For instance, Haynes and Christ (1999) reported much higher heritability estimates for late blight resistance (0.8), but this study was based on diploid hybrids. For the same trait, estimates of heritability obtained using tetraploid genotypes are closer to the ones reported here (ranging from 0.31 to 0.69, Pajerowska-Mukhtar et al 2009 ; Solano et al 2014 ).…”
Section: Discussionsupporting
confidence: 80%
“…The landraces under study showed different responses to late blight in the experimental field. Most of them turned out to be moderately resistant to susceptible (Table 1), which is in line with reports on landraces from other parts of the Andes (Perez et al, 2014;Solano et al, 2014). Five landraces (one diploid and four tetraploid) showed the best field resistance.…”
Section: Ecuadorian Landraces and Late Blight Performancesupporting
confidence: 89%
“…In accordance to the results of Colon et al (1995) [14] which consider that the most important resistance components in Solanum tuberosum are efficiency of infection (equivalent to the probability of infection success), growth rate of the lesion and sporulation capacity, R-8906384 the resistant control and UCT-34Cor which had the best performance in the field trials revealed the highest performance for these three components. This accession achieved one of the highest resistance to the disease under field conditions and showed one of the lowest values AUDPCr (AUDPCr: 0.05) [27]. We also found a positive correlation between the probability of in vitro infection and the AUDPCr measured in the field.…”
Section: Resultssupporting
confidence: 64%